Utilization of barley straw by steers: Effects of replacing urea with protein, source of protein and quantity of rumen degradable nitrogen on straw degradation, liquid and particle passage rates and intake - Nsahlai, I.V.; Bryant, M.J.; Umunna, N.N. (Informa UK Limited, 1999)
The study aimed at examining the effects of replacing urea with protein nitrogen (N), source of protein and the quantity of rumen degradable N (RDN) in the diets of steers on rumen fermentation, outflow rate and intake. In experiment one, six ruminally cannulated Friesian steers were used in a replicated 3x3 latin square experiment to evaluate the effects of replacing urea N with rapeseed N (0.25, 0.50 and 0.75) on degradation, outflow rate and intake. In experiment two, six ruminally cannulated steers were used in a 3 (2x2) latin square experiment to compare fish (FM) and rapeseed meals (RSM) in the context of the above variables. In both trials, diets contained adequate RDN (1.66-2.11g/MJ ME) and sulphur (0.133-0.157 g/g RDN). Increased level of protein-N was associated with decreased (p<0.001) ruminal ammonia, but had no effect on intake, degradation rate, particulate (k), or liquid (kL) or liquid (KL) outflow rates. FM induced lower (p<0.05) KL than RSM, but both diets had similar intake, degradation rate, K1 and rumen ammonia. Intake and kL increased linearly while degradation increased quadratically with dietary RDN. In addition an equation (K1 = 0.3006 W -0.5103 SPROP 0.535) was proposed for predicting particle rate of passage in supplemented animals, where W=live weight and SPROP = supplement proportion). It was concluded that (1) when a diet containing high RDN is adequately supplemented with sulphur, providing 0.25 of supplementary N as protein is enough to sustain optimum degradation rate and intake of straw, (2) the positive effect of optimum RDN and of by-pass protein on digestibility and rumen fill, respectively, are not additive for steers fed a good quality roughage and (3) 1.83 g RDN/MJ ME is that which is required to maximize straw degradation rate.